2017
DOI: 10.3390/children4050031
|View full text |Cite
|
Sign up to set email alerts
|

Mind–Body Therapy for Children with Attention-Deficit/Hyperactivity Disorder

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is pervasive among the pediatric population and new treatments with minimal adverse effects are necessary to be studied. The purpose of this article is to review current research studying mind–body therapies for treatment of children diagnosed with ADHD. Literature was reviewed pertaining to the effectiveness of movement-based therapies and mindfulness/meditation-based therapies for ADHD. Many positive effects of yoga, Tai Chi, physical activity, and meditation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 53 publications
0
28
0
Order By: Relevance
“…Attention deficit/hyperactivity disorder (ADHD) is the most prevalent neurobehavioral disorder among children . Boys are two to nine times more likely than girls to develop ADHD .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Attention deficit/hyperactivity disorder (ADHD) is the most prevalent neurobehavioral disorder among children . Boys are two to nine times more likely than girls to develop ADHD .…”
Section: Introductionmentioning
confidence: 99%
“…There are different reports on ADHD incidence rates. For example, Kaplan and Sadock reported that over 50% of the visits to children's psychiatric outpatient clinics and 3–5% of the school‐age children include the children with ADHD . Also, Pineda, Biederman, and Catherine have reported the general incidence rate of this disorder as 16.4%, 8–10%, and 6.5%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations